Factors Affecting Nurse Performance at Two Public Hospitals in South Kalimantan - Noor, Sirajudin; Nursalam, Nursalam; Sukartini, Tintin; Nasri, Novi Mustahdiati; Setiawan, Herry; Agianto, Agianto (International Journal of Psychosocial Rehabilitation, 2020)
Many factors affect nurses’ performance while working in hospitals. Knowing the dominant factors affecting a nurse's performance can help to identify the right policy to improve the quality of health services. Low nurse performance has an impact on the quality of services. In addition, the low performance of nurses also causes an increase in the expenses in the hospital. It is more than 5% of annual operating costs. The purpose of this study was to identify the factors that affect nurses’ performance at two public hospitals in South Kalimantan. A quantitative research with cross-sectional approach was used involving 150 samples with consecutive sampling techniques from July to September 2019. Multivariate analysis of multiple logistic regression was used to identify the dominant factors affecting the nurses’ performance. Factors that influence it are nurses’ last education (0.06), and nurses' commitment to the hospital (0.00). Hospitals need to program further education and training for nurses to improve a good work climate and make commitments to improve nurse performance and quality of care in public hospitals in South Kalimantan.